1994
DOI: 10.1002/lsm.1900140304
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of photodynamic therapy with photofrin in the normal rat brain

Abstract: The widespread acceptance of photodynamic therapy (PDT), a potential adjuvant brain tumor therapy under clinical evaluation since 1980, has been partially restrained by its potential toxicity toward normal brain tissue. This study examined PDT-produced injury of normal rat brain as a function of photosensitizer dose. Brain injury was characterized by correlating measurements of the area of cerebral edema using T2-weighted magnetic resonance images, measurement of brain water content at the lesion site, microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Evidence to date (Dereski et al, 1991;Chen et al, 1992a,b;Lilge et al, 1993a;Ying et al, 1994) suggests that the photodynamic threshold model holds also for intracranial tissues. Kaye and Morstyn (1987), using haematoporphyrin derivative (HpD) at 20 mg per kg body weight (bw) and 200 J cm-2 of surface light dose, and Sandeman et al (1987), using trisulphonated aluminium chlorophthalocyanine at 0.5 mg per kg bw and 700 J cm-2, observed selective tumour kill in intracranial murine tumour models, while normal brain tissue showed no, or very limited necrosis under these treatment conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence to date (Dereski et al, 1991;Chen et al, 1992a,b;Lilge et al, 1993a;Ying et al, 1994) suggests that the photodynamic threshold model holds also for intracranial tissues. Kaye and Morstyn (1987), using haematoporphyrin derivative (HpD) at 20 mg per kg body weight (bw) and 200 J cm-2 of surface light dose, and Sandeman et al (1987), using trisulphonated aluminium chlorophthalocyanine at 0.5 mg per kg bw and 700 J cm-2, observed selective tumour kill in intracranial murine tumour models, while normal brain tissue showed no, or very limited necrosis under these treatment conditions.…”
mentioning
confidence: 99%
“…Several authors (Cheng et al, 1984;Dereski et al, 1991;Chen et al, 1992a;Leach et al, 1993;Ying et al, 1994) have noted a very high sensitivity of normal brain tissue to PDT using Photofrin as photosensitiser. The first histologically observable changes in normal brain are in structures associated with the BBB, such as endothelial cell damage (Berenbaum et al, 1986) and astrocytic swelling (Yoshida et al, 1992a).…”
mentioning
confidence: 99%
“…Photoactivation of the HPD produces vascular toxicity resulting in a further increase in blood brain barrier permeability, erythrocyte extravasation, and intravascular thrombosis. Recently, by using the same experimental model, it was shown that the blood brain barrier permeability change after PDT is directly related to the dose of Photofrin administered [21]. Obviously, ischemia, secondary to vascular thromboses caused by PDT, is one of the mechanisms by which PDT kills the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tumors are the most common solid cancers in the pédiatrie age group, the third leading cause of cancer death in the [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] year age group12 and the sixth most common cause of cancer mortality in the population over the age of 20.3 Furthermore, there appears to be either an increase in the incidence of malignant brain tumors among the elderly population4 and/or an increase in the rate of recognition of brain tumors with improved imaging capabilities.5 In spite of surgical resection and aggressive adjuvant radiotherapy and/or chemotherapy, the prognosis for these patients remains poor.…”
Section: Introductionmentioning
confidence: 99%